The Agile practice guide. (The Project Management Institute, 2017)
"The Project Management Institute and Agile Alliance® chartered this practice guide to create a greater understanding of Agile approaches in their communities. The vision for this practice guide is to equip project teams with tools, situational guidelines, and an understanding of the available Agile techniques and approaches to enable better results. Project teams are using Agile approaches in a variety of industries beyond software development. Both organizations realize that expansion has created a need for a common language, open mindedness, and the willingness to be flexible in how products and deliverables are brought to market. In addition, both organizations realize there are multiple ways to achieve successful delivery. There are a broad range of tools, techniques, and frameworks; teams have choices for approaches and practices that fit their project and the organizational culture in order to achieve the desired outcome. The Agile Practice Guide core committee members are from varying backgrounds and use various approaches. Some of the committee members are consultants and some work inside organizations. All have worked in Agile ways for many years"--